DETERMINANTS OF THE QUALITY OF PHARMACY SERVICES IN HOSPITAL DURING PANDEMIC COVID-19 - Arie Sulistiyoningrum; Ayun Sriatmi; Septo Pawelas Arso (Dentino : Jurnal Kedokteran Gigi, 2022)
Background. Hospitals are individual health service facilities that are part of health resources in order to support the implementation of health efforts, one of which is pharmacy services. During pandemic covid-19, all hospitals must continue to provide service to patients,  according to technical instructions, including Aisyiyah Kudus Hospital. The quality of service is determined by various factors, including perception of hospital, facilities, policies and competencies. Purpose. This study aims to analyse factors that affect quality of pharmaceutical services in the outpatient pharmacy installation of Aisyiyah Kudus Hospital. Methods. This study was a quantitative study with cross sectional design, population in this study were outpatients who received pharmacy services at Aisyiyah Kudus Hospital with sample size of 98 respondents. Sampling technique in this study was accidental sampling. Data were analysed by using Chi-Square test and Logistic Regression. Results. The result shows that there is a significant relationship between perceptions of hospital, infrastructure, officer competence and policies with service quality with p value 0.000, in a regression analysis show that there is a very strong influence of independent variables on the dependent variable. Conclusion. There is a significant relationship between perceptions of hospital, infrastructure, officer competence and policies with service quality. Hospital management needs to provide soft skill training for all officers in supporting the improvement of services to patients